Resilience With The Level of Anxiety of Pregnant Women During The Covid-19 Pandemic in Tourism Destination Area in Buleleng District - Made Bayu Oka Widiarta; Hesteria Armynia Subratha; Wigutomo Gozali; I Nyoman Suardyatma; Putu Sukma Megaputri; Putu Suryani (Jurnal Smart Keperawatan, 2022)
During the Covid-19 pandemic, many Tourism Destination Areas (DTW) were affected, one of which was a decrease in visits and a decline in the community's economy, causing many psychological problems, especially for groups of pregnant women. The handling of this problem has not been carried out by related parties. The aim is to determine the relationship between resilience and the anxiety level of pregnant women in the tourist destinations of Pemuteran Village and Pejarakan Village. The cross-sectional approach used a sample of 72 pregnant women. Sampling technique with non-probability sampling with purposive sampling. Data collection used a standardized questionnaire measuring anxiety levels Hamilton Anxiety Rating Scale (HARS), and resilience measurement using The Connor-Davidson Resilience questionnaire (CD-RISC). Univariate analysis to determine the characteristics data and demographic data, and bivariate analysis Spearman's Rank test. The results showed that most of the respondents showed an anxiety level in the mild category, 55 people (76.4%). The level of resilience of majority of respondents has a high level of resilience, namely 52 people (72.2%). There is a significant relationship between high resilience associated with decreased anxiety with a p-value of 0.001 <0.05 with a value of r = -606. The higher the resilience, the lower the anxiety level of pregnant women.                                                                                                                                           Keywords: resilience; anxiety; pregnant mother; tourist destination area; the covid-19 pandemicResiliensi Dengan Tingkat Ansietas Ibu Hamil Selama Pandemi Covid-19 Di Daerah Tujuan Wisata Kabupayen BulelengABSTRAKMasa pandemi covid-19 banyak kawasan Daerah Tujuan Wisata (DTW) yang terdampak salah satunya yaitu penurunan kunjungan dan merosotnya perekonomian masyarakat sehingga banyak menimbulkan masalah psikologis terutama pada kelompok ibu hamil. Penanganan masalah ini belum dilaksanakan oleh pihak terkait. Tujuan untuk mengetahui hubungan resiliensi dengan tingkat ansietas ibu hamil pada daerah tujuan wisata Desa Pemuteran dan Desa Pejarakan. Pendekatan cross sectional menggunakan sampel sebanyak 72 ibu hamil. Teknik sampling dengan non probability sampling dengan purposive sampling. Pengumpulan data menggunakan kuesioner baku dari pengukuran tingkat cemas  Harmilton Anxiety Rating Scale (HARS), data dan pengukuran resiliensi menggunakan kuesioner The Connor-Davidson Resilience (CD-RISC). Analisa univariat mengetahui data karakteristik dan data demografi, analisis bivariat uji Rank Spearman. Hasil menunjukkan sebagian besar responden menunjukkan tingkat ansietas dalam kategori ringan sebanyak 55 orang (76,4%). Tingkat resiliensi responden mayoritas memiliki tingkat resiliensi tinggi yaitu 52 orang (72,2%). Terdapat hubungan yang signifikan antara resiliensi yang tinggi berhubungan dengan penurunan kecemasan dengan nilai p 0.001 < 0.05 dengan nilai r = -606. Semakin tinggi resiliensi maka semakin rendah tingkat ansietas ibu hamil.Kata Kunci : resiliensi; ansietas; ibu hamil; daerah tujuan wisata; pandemi covid-19